Age-related differences of subjective visual vertical perception in adults—a functional near-infrared spectroscopy study - Lu, Jun; Gong, Xiang; Wang, Meng-Huan; Zhao, Ruo-Xin; Wang, Yu-Chen; Shen, Ying-Ying; Cao, Rong; Xu, Guang-Xu (Frontiers in Aging Neuroscience, 2025)
BackgroundThe perception of Subjective Visual Vertical (SVV) is crucial for postural orientation and significantly reflects an individual’s postural control ability, relying on vestibular, visual, and somatic sensory inputs to assess the Earth’s gravity line. The neural mechanisms and aging effects on SVV perception, however, remain unclear.ObjectiveThis study seeks to examine aging-related changes in SVV perception and uncover its neurological underpinnings through functional near-infrared spectroscopy (fNIRS).MethodsIn a comparative study of 19 young and 19 older adults, the standardized SVV task executed in Eprime 3.0 software evaluated participants’ SVV orientation and uncertainty. Cortical responses were monitored via fNIRS during the task, with block averaging analysis employed to delineate the associated hemodynamic responses. The study further correlated these neuroimaging findings with behavioral measures.ResultsYoung individuals exhibit superior accuracy and stability in perceiving the subjective visual vertical (SVV) direction. Neuroimaging data, adjusted for multiple comparisons using the false discovery rate, reveal activation of the right supramarginal gyrus (SMG) and the left dorsolateral superior frontal gyrus (SFGdor) in both age groups during SVV tasks. However, older participants show additional activation in regions such as the bilateral postcentral gyrus (PoCG) and the right middle frontal gyrus (MFG). Lateralization studies indicate that young participants predominantly exhibit right lateralization in sensory and dorsolateral prefrontal cortices, with left lateralization in the motor cortex. In contrast, elderly participants demonstrate bilateral dominance across sensory, dorsolateral prefrontal, and motor cortices. Correlational analyses link modified SVV metrics to the activation levels of various brain regions, with negative correlations observed in both age groups, and a unique positive correlation with the left inferior frontal gyrus of the triangular part (IFGtriang) in young participants.ConclusionYoung individuals outperform the older individuals in SVV performance due to age-related differences in brain functional patterns during the execution of vertical perception judgment. Both age groups activate the right SMG and left SFGdor, but the older individuals additionally activate regions such as bilateral PoCG and right MFG. While young people exhibit right-brain dominance, the older people rely on bilateral cognitive resources, indicating bilateral dominance. Except for the left IFGtriang in the young, higher activation in brain regions correlates with better SVV performance.